2002
DOI: 10.1152/ajprenal.00363.2001
|View full text |Cite
|
Sign up to set email alerts
|

Decreased renal heme oxygenase-1 expression contributes to decreased renal function during cirrhosis

Abstract: Heme oxygenase (HO) is the rate-limiting enzyme in the degradation of heme, catalyzing the oxidative cleavage of heme molecules to biliverdin, carbon monoxide, and iron. The present study was designed to investigate the role of HO-1 in the pathogenesis of renal dysfunction during cirrhosis. Biliary cirrhosis was induced in rats by common bile duct ligation (CBDL). Animals were studied 2 and 5 wk after surgery. In kidney from CBDL rats, HO-1 protein expression increased slightly at 2 wk but was abolished at 5 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 33 publications
3
20
0
Order By: Relevance
“…In kidneys from CBDL rats, Miyazono et al [73] have shown that HO-1 protein expression is increased slightly at 2 wk but is abolished at 5 wk. In addition, histologically, HO-1 expression was suppressed in renal tubules and interlobular arterioles in 5-wk-old CBDL rats.…”
Section: Cirrhotic and Pre-hepatic Portal Hypertensionmentioning
confidence: 99%
See 1 more Smart Citation
“…In kidneys from CBDL rats, Miyazono et al [73] have shown that HO-1 protein expression is increased slightly at 2 wk but is abolished at 5 wk. In addition, histologically, HO-1 expression was suppressed in renal tubules and interlobular arterioles in 5-wk-old CBDL rats.…”
Section: Cirrhotic and Pre-hepatic Portal Hypertensionmentioning
confidence: 99%
“…Renal HO-1 expression is decreased in cirrhotic rats (bile ligation) in renal tubules and interlobular arterioles, while it is increased in the liver. The decreased HO-1 is related to renal dysfunction [73] . During HPS caused by liver cirrhosis, pulmonary endothelial NOS expression and NO production are increased.…”
Section: Cirrhotic and Pre-hepatic Portal Hypertensionmentioning
confidence: 99%
“…Rats weighing 286 Ϯ 12 g were divided into the following six groups: (i) saline group (control group), rats receiving 3 ml/kg 0.9% NaCl, intraperitoneally (i.p. ), once a day for 5 days; (ii) hemin group, rats receiving 10 mg/kg hemin (11), i.p., once a day for 5 days; (iii) ZnPP group, rats receiving 50 mol/kg zinc protoporphyrin (27), i.p., on day 5; (iv) PMB group, rats receiving 4 mg/kg PMB (10), i.p., once a day for 5 days; (v) PMB plus hemin group, rats receiving 4 mg/kg PMB, i.p., plus 10 mg/kg hemin, i.p., once a day for 5 days; and (vi) PMB plus ZnPP group, rats receiving 4 mg/kg PMB, i.p., once a day for 5 days, plus 50 mol/kg ZnPP, i.p., administered before PMB on day five.…”
Section: Chemicals and Reagentsmentioning
confidence: 99%
“…23 Under our conditions, control experiments indicated that the effective dose of ZnPP (which inhibited HO-1) was 20 mg/kg. Although the exact half-life in the circulation of ZnPP is unknown, 58 the plasma ZnPP concentration remained elevated for 2-3 days after a single dose of 25 mg/kg i.p. 59 In regards to SB203580, the elimination half-life of this drug (2.1 mg/kg i.v.)…”
Section: 34mentioning
confidence: 99%